A novel transthyretin Lys70Glu (p.Lys90Glu) mutation presenting with vitreous amyloidosis and carpal tunnel syndrome. (2nd January 2016) - Raivio, Virpi Elisa; Jonasson, Jenni; Myllykangas, Liisa; Ala-Mello, Sirpa; Kankuri-Tammilehto, Minna; Kiuru-Enari, Sari; Westermark, Per; Tanskanen, Maarit; Kivelä, Tero
Abstract: Objective : We describe a novel TTR mutation with vitreous opacities and carpal tunnel syndrome. Materials and methods : A 78 year-old woman with vitreous opacities, her daughter with dry eye syndrome, and brother with carpal tunnel syndrome were tested for a mutation in the TTR gene. The vitreous opacities were removed and stained with Congo red and immunohistochemistry against wild type TTR. Skin and gut biopsies and specimens of soft tissue were examined histopathologically. Leukocyte DNA from the proband was analysed by direct sequencing of exons 1 to 4 of the TTR gene and DNA from her daughter and brother using segregation analysis. Results : A point mutation c.268 A>C, in the TTR gene, leading to a missense mutation p.Lys90Glu was found in all subjects. The vitreous opacities were pearl string-like. Histopathology showed red to green birefringence in Congo red, typical to amyloid, and the specimens were immunoreactive with antibodies against TTR. Conclusion : We present a novel autosomally inherited Lys90Glu mutation in the TTR gene. This is the first reported FAP family with this mutation in Finland.